2020
DOI: 10.1021/acs.langmuir.0c01268
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Pathways to Equilibrate Langmuir Polymer Films

Abstract: Focusing on the phase-coexistence region in Langmuir films of poly­(l-lactide), we investigated changes in nonequilibrated morphologies and the corresponding features of the isotherms induced by different experimental pathways of lateral compression and expansion. In this coexistence region, the surface pressure Π was larger than the expected equilibrium value and was found to increase upon compression, i.e., exhibited a nonhorizontal plateau. As shown earlier by using microscopic techniques [Langmuir 2019, 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 68 publications
3
15
0
Order By: Relevance
“…By compressing the Langmuir film from A 1 to A 4 , significant changes in the order of this arrangement were observed as a function of increasing surface density (see Figure ). Interestingly, in addition to the distinctive differences discussed below, the morphology of the filaments was somewhat similar to the one observed for the homopolymer P l LA 1840 (see also Figure S2 of the Supporting Information) . Thus, it is quite reasonable to assume that the formation of filaments was influenced or even governed by the P l LA block.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…By compressing the Langmuir film from A 1 to A 4 , significant changes in the order of this arrangement were observed as a function of increasing surface density (see Figure ). Interestingly, in addition to the distinctive differences discussed below, the morphology of the filaments was somewhat similar to the one observed for the homopolymer P l LA 1840 (see also Figure S2 of the Supporting Information) . Thus, it is quite reasonable to assume that the formation of filaments was influenced or even governed by the P l LA block.…”
Section: Resultssupporting
confidence: 67%
“…Therefore, the kinetics of compression and expansion as well as constraints imposed by the geometry of the Langmuir trough will affect the hysteresis loops. 18 However, the study presented here clearly shows that the observed changes in morphology were reversible and were controlled by surface density.…”
Section: ■ Results and Discussionmentioning
confidence: 58%
See 3 more Smart Citations